Health literacy and loneliness among physically inactive Danes aged 18–65: a cross-sectional study - Sarmanlu, Delal; Heuck, Iben Rask; Maindal, Helle Terkildsen; Lim, Michelle H.; Ryom, Knud (Frontiers in Public Health, 2024)
Introduction: Both physical inactivity and loneliness are public health threats bringing huge costs to society and quality of life. The two health challenges often co-exist, suggesting physically inactive and lonely individuals' to be a high-risk group. Health literacy as a concept is understood as a modifiable health determinant, and it has been proposed for promoting equity in future health promotion. Aim: The aim of this study is to examine the association between health literacy and loneliness among physical inactive adults. Methods: A representative sample of 6,196 Danish adults, aged 18-65 years, were invited to a screening on a set of health outcomes for physical inactivity.Which was based on the International Physical Activity Questionnaire-Short Form. A total of 1,033 adults were classified as physically inactive and therefore received the full questionnaire screening on a set of different health outcomes including the Health Literacy Questionnaire (HLQ) and the Three-Item Loneliness Scale (T-ILS). Two statistical approaches were applied: 1) Health literacy expressed as nine different continuously variables corresponding to the domains of HLQ using logistic regressions analyses to examine association between health literacy and loneliness; 2) Health literacy expressed as nine different binary variables showing proportions of low literacy among lonely versus non-lonely participants. Statistical analyses were performed in Stata/IC version 16.1. Results: Among a sample of 1010 physically inactive, 23.7% felt lonely with a T-ILS score below ≥7.Regression analyses predicted a negative association between health literacy and loneliness in all HLQ-domains, after adjusting for gender, age, education, and occupation. Adjusted ORs in domain 1-5 ranged from 0.21 (95% CI: 0.16;0.27) to 0.69 (95% CI:0.57;0.83) and in domain 6-9 from 0.50 (95% CI:0.41;0.61) to 0.70 (95% CI:0.55;0.89). A similar pattern was found in the analysis with health literacy as a binary variable as the proportions of low health literacy were highest among persons with loneliness in all HLQ-domains. Conclusion: Even after adjusting for sociodemographic factors, a negative association was predicted between health literacy and loneliness in physically inactive adults. This suggests that strategies for improving physical activity among inactive individuals may benefit from having a focus on health literacy and loneliness. .